A crítica da moralidade de Bernard Williams: identidade moral, tragédia e responsabilidade ética - Wendell Pereira Barreto Garcez (2023)
This dissertation aims to undertake a genealogical effort to understand Bernard Williams' critique of morality in his philosophical project. The study seeks to carry out this effort of understanding from three major axes of the author's work. First, we must understand how his considerations on personal identity were constructed and how, through dialogue with his critics, it is possible to perceive the insertion of the personal identity debate in the field of moral philosophy: according to the author, it is not possible to establish an adequate criterion of personal identity without considering the material relationships and historical context in which the individual is inserted. Secondly, we must understand how Williams used the concept of personal integrity, a concept that I believe is inherent to the debate on personal identity, to criticize utilitarian doctrines: for Williams, utilitarianism demands the violation of personal integrity and moral identity of the individual for the benefit of the principle of utility in practical deliberation. Finally, we must understand how Kantian morality, despite also offering criticisms of utilitarianism, also ends up violating personal integrity, demanding that the subject give up their moral character, or their personal projects, commitments, and beliefs, in favor of external moral reasons. In addition, this study also aims to demonstrate how certain moral residues of practical deliberation, such as tragedy, moral regret, and their respective pedagogical roles, are habitually ignored by both utilitarian and Kantian moral doctrines. In the end, it will be demonstrated how morality, as an externalist system of reasons, can be harmful, impoverishing moral philosophy and establishing a deliberative logic that underestimates the capacity of individuals. However, it cannot be completely dismissed, as it can offer a powerful tool for improving deliberative reasons, on the condition of a new meaning of its importance in political life